2007
DOI: 10.1074/jbc.m703466200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Blocks the Activity of Tubulin Polymerization-promoting Protein (TPPP)

Abstract: Tubulin polymerization-promoting protein (TPPP), an unfolded brain-specific protein interacts with the tubulin/microtubule system in vitro and in vivo, and is enriched in human pathological brain inclusions. Here we show that TPPP induces tubulin self-assembly into intact frequently bundled microtubules, and that the phosphorylation of specific sites distinctly affects the function of TPPP. In vitro phosphorylation of wild type and the truncated form (⌬3-43TPPP) of human recombinant TPPP was performed by kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
109
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 62 publications
(116 citation statements)
references
References 38 publications
6
109
1
Order By: Relevance
“…It has been reported that phosphorylation of TPPP inhibits its tubulin polymerizing activity (Acevedo et al, 2007;Hlavanda et al, 2007). Therefore, our data suggest that under normal circumstances, LIMK2 present at the mitotic spindle phosphorylates TPPP and prevents excessive tubulin polymerization, thus, controlling the number of astral microtubule filaments.…”
Section: Discussionmentioning
confidence: 64%
“…It has been reported that phosphorylation of TPPP inhibits its tubulin polymerizing activity (Acevedo et al, 2007;Hlavanda et al, 2007). Therefore, our data suggest that under normal circumstances, LIMK2 present at the mitotic spindle phosphorylates TPPP and prevents excessive tubulin polymerization, thus, controlling the number of astral microtubule filaments.…”
Section: Discussionmentioning
confidence: 64%
“…Our recent study established that Rock-mediated phosphorylation of Tppp1 inhibits its interaction with Hdac6 resulting in decreased MT acetylation in cells without altering Tppp1-mediated MT polymerization (4). Tppp1 is highly phosphorylated in cells on residues distinct from the Rock-mediated sites raising the possibility that its MT polymerizing activity is regulated by other kinases and signaling pathways (5)(6)(7)(8)(9)(10).…”
mentioning
confidence: 99%
“…In pathological conditions, TPPP/p25 is enriched in filamentous ␣-synuclein-bearing Lewy bodies of Parkinson disease (PD) 2 and diffuse Lewy body disease (5) as well as in glial cytoplasmic inclusions from multiple system atrophy brain tissues (6). TPPP/p25 polymerizes tubulin in vitro into normal and aberrant microtubules depending on its concentration and its phosphorylation state (7,8). When expressed at low level in transfected HeLa cells, TPPP/p25 colocalizes specifically with the microtubules and induces microtubule bundling (9).…”
mentioning
confidence: 99%